1999
DOI: 10.1023/a:1021863901603
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Although Salvadoreans are the fourth largest group of Hispanics in the United States, little is known about their cancer knowledge, attitudes, and practices. There are no publications assessing cancer knowledge among Salvadorean men. In this cross-sectional survey, information was gathered from 706 immigrant Salvadorean men in Washington, D.C. The majority of these men knew that smoking causes cancer and that some cancers can be cured if detected early. However, the men in this survey had inadequate knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The review found wide differences in beliefs both between countries, but also across ethnic and cultural groups within countries. Psychological factors such as fatalism, fear and embarrassment were identified as possible barriers to help seeking (Long, 1993; Frisby, 2002; Lannin et al , 2002), while lack of knowledge about cancer symptoms or early detection methods and misconceptions about causal processes also play a part (Gregg and Curry, 1994; Ratnasinghe et al , 1999). A recent qualitative study indicated that black and ethnic minority groups had poor knowledge about cancer, as well as beliefs and attitudes that might reduce attendance at services designed to promote early diagnosis (Thomas et al , 2005).…”
mentioning
confidence: 99%
“…The review found wide differences in beliefs both between countries, but also across ethnic and cultural groups within countries. Psychological factors such as fatalism, fear and embarrassment were identified as possible barriers to help seeking (Long, 1993; Frisby, 2002; Lannin et al , 2002), while lack of knowledge about cancer symptoms or early detection methods and misconceptions about causal processes also play a part (Gregg and Curry, 1994; Ratnasinghe et al , 1999). A recent qualitative study indicated that black and ethnic minority groups had poor knowledge about cancer, as well as beliefs and attitudes that might reduce attendance at services designed to promote early diagnosis (Thomas et al , 2005).…”
mentioning
confidence: 99%